"Get it out the way. The wait's killing me." hastening and hiding during soccer penalty kicks - Furley, P.; Dicks, M.; Stendtke, F.; Memmert, D. (Psychology of Sport and Exercise, 2012)
Objectives: It has been suggested that hastening and hiding—rushing through penalty preparation and not looking at the goal when preparing the penalty kick—are associated with negative penalty taking performance. In the present study, we investigated how opposing players perceived these nonverbal behaviors, how they affect outcome expectations, and how they affect the behavior of opposing goalkeepers. Design: The present study employs an experimental research design (Experiment 1: 2 (gaze behavior) × 3 (preparation time) design; Experiment 2: 2 (gaze behavior) × 2 (preparation time) design). Method: We examined the perception of nonverbal hastening and hiding behavior using the point-light technique during the soccer penalty kick among goalkeepers (Experiment 1a; n = 20), and among outfield soccer players (Experiment 1b; n = 29). Furthermore, we analyzed how these respective penalty preparation strategies influenced the behavior of high-level goalkeepers (n = 12) under in situ conditions (Experiment 2). Results: The results from Experiment 1 demonstrated that penalty takers showing hastening and hiding behaviors are perceived more negatively by both soccer goalkeepers and outfield players: (i) they are considered to possess less positive attributes, (ii) to have less accuracy in their penalties, and (iii) likely to perform less well in penalty situations. Experiment 2 provided first evidence that goalkeepers initiate their movement later following the observation of hastening and hiding behaviors during the penalty preparation. Conclusions: Our findings demonstrate the importance of investigating nonverbal behavior in sports as these have a major impact on impression formation, expected performance, and actual behavior of opposing players in the soccer penalty situation.